Study of the Transformation of New Forms in Development National Gallery of Indonesia - Agus Budi Purnomo; Asep Rohman Hidayat; Rita Walaretina (International Journal of Engineering, Science and Information Technology, 2022)
The transformation of existing buildings at the National Gallery of Indonesia has undergone several transitions, ranging from colonial residences and educational spaces to exhibition spaces. This transitional need became an important consideration in terms of the function and identity of the word ‘National’ contained in it until finally, a proposal for the development of the National Gallery of Indonesia in 2013 was initiated, which focuses on exploring the mass of new buildings that support exhibition spaces with conservation considerations in mind. The form of the mass becomes visually unimportant because it can give a provocative and inviting impression. References are based on mass transformation, new mass response to sustainable buildings, and visual response to the front area. This research aims to explore new building forms of the National Gallery, which can be considered in the subsequent development process and the discourse on architectural forms in development buildings with elongated tread characters and sustainable buildings in the middle. The research method uses literature research and case studies. The data collection technique was carried out by literature observation. It was concluded that the eight study samples did not simultaneously have the second criterion (contrast - symmetric or dynamic - proactive) but rather the configuration form of the four criteria. Consideration of balanced form is dominant rather than different balance. While the application of rhythm is found in the principle of height difference resulting from the mass transformation process.